Psychosocial Long-Term Effects of Young Adult Cancer Survivors: Study Protocol of the Longitudinal AYA-LE Long-Term Effects Study - Geue, Kristina; Mehnert-Theuerkauf, Anja; Stroske, Isabelle; Brock, Hannah; Friedrich, Michael; Leuteritz, Katja (Frontiers in Psychology, 2021)
Background: About 3% of new cancer cases affect young adults aged between 15 and 39 years. The young age, the increasing incidence and the relatively good prognosis of this population lead to the growing importance to investigate the psychosocial long-term and late effects. The aims of the AYA-LE long-term effects study are: first, to assess the temporal course and related factors of life satisfaction and psychological distress of adolescent and young adult (AYA) cancer survivors; and second, to examine a specific topic in each of the yearly surveys in a more differentiated way. Methods: This study represents a continuation of the longitudinal AYA-LE study (Leuteritz et al., 2017). The existing sample of AYA cancer patients (t1: N=577; t2: N=514; aged between 18 and 39 years at diagnosis; all major tumour entities) was extended by four further survey points (t3: 2018, t4: 2019, t5: 2020, t6: 2021). In addition, a comparison sample of young adults without cancer was collected. We measured longitudinal data for outcomes such as quality of life, psychological distress, and fatigue with standardized questionnaires. Furthermore, each survey point included a different cross-sectional topic (e.g. health behaviour, occupational situation, and compliance). Discussion: The AYA-LE long-term effects study will show the long-term consequences of cancer in young adulthood. We expect at least 320 complete datasets to be available after the sixth survey, which will be completed in 2021. This will provide a comprehensive and differentiated understanding of the life situation of young adults with cancer in Germany. The findings of our study enable a continuous improvement of the psychosocial care and specific survivorship programmes for young cancer patients.